The impact of the concepts of lean manufacturing on the strategies of the supply chain - Kazmane, Jaouad; Chafi, Anas; Tajri, Ikram; En-nadi, Abdelali (International Journal of Engineering and Technology, 2014)
In a highly competitive environment, cost reduction and optimization of the supply chain are more than ever a strategic issue for companies. In this sense, lean manufacturing is a lever that allows the company to continuously reduce the time required for the transformation of raw materials into finished products, eliminating waste and with the aim to meet the growing and diverse needs of these customers.In this paper, it based on the latest studies in this field in order to highlight the relationship between supply chain and lean manufacturing at reducing costs, eliminating waste and non-value added. Then it highlights the impact of lean manufacturing on the reactivity of the supply chain through inventory reduction, cycle time and flow acceleration. Finally, it presents the role and expectations of the supplier in the context of the merger Lean Manufacturing and Supply Chain.This research has enabled to understand the impact of lean manufacturing concepts on supply chain strategies.
Keywords: Acceleration of the Flow; Cycle Time; Lean Manufacturing; Stock Reduction; Supply Chain.